Cereal biotechnology - Morris, Peter C.; Bryce, James H. (CRC Press ; Woodhead Pub., 2000)
More than 50% of the world's food comes from the three cereals: wheat, maize, and rice. In order to continue to feed a growing world population the food industry must understand the potential benefits that cereal biotechnology can offer. This collection provides a bridge between academic theory on the potential of this technology and the industrial aspects of current practice. The individual chapters provide coverage of product development, specific applications, current regulation, and the question of consumer acceptability.
Keywords: Grain -- Biotechnology.; elektronické knihy; electronic books